PEMANFAATAN ITERATED FUNCTION SYSTEM (IFS) UNTUK MEMBANGKITKAN MOTIF ANYAMAN UKURAN n x n - Maris, Ingka; Purnomo, Kosala Dwidja; Juliyanto, Bagus (Majalah Ilmiah Matematika dan Statistika, 2021)
Woven is one of art thats very close to life. Woven has a pattern consisting of two-dimensional (2D) and has a basic pattern. Along with the development times, technology is also growing including computer technology. Computer can be used for mathematical calculation process, one of them is fractal. Fractal Sierpinski carpet is formed from a square that use Iterated Function System (IFS) method. This method is exact self-similar resulting in the same fractal with the original constituent object. The writer want to get woven pattern using computer technology, that is GUI application in Matlab that utilizes the IFS method on fractal. Woven patterns formed from woven that have a grid size of n x n and are given a few iterations. So, that it can make it easier for craftsmen to make woven pattern that are interesting and varied.